Differences of spinal cord gadolinium enhancement features of neuromyelitis optica spectrum disorder and long-segment degenerative cervical myelopathy - Sun, Xingwen; Zhao, Qiang; Zhang, Lihua; Yuan, Huishu (Frontiers in Neurology, 2023)
Objectives: Neuromyelitis Optica Spectrum Disorder (NMOSD) and long-segment degenerative cervical myelopathy (DCM) may have similar appearance on MRI. This study is to identify the differences of spinal cord gadolinium enhancement features between NMOSD and long-segment DCM. Methods: Spinal cord gadolinium enhancement of 27 NMOSD patients and 30 long-segment DCM patients were retrospectively analyzed. Enhancements were evaluated for their number, length, location on the sagittal images, distribution on the axial images, and form on the sagittal images. Wilcoxon rank sum tests were performed to compare numerical variables. Pearson chi-square tests were performed to compare categorical variables. Results: The median number of enhanced lesions (p<0.05), the median length of the enhancements (p<0.05), and the location of enhancement on sagittal images (p<0.05) of NMOSD patients and long-segment DCM patients showed significant differences. The axial distribution of enhancements didn’t show significant difference between NMOSD and long-segment DCM patients (p=0.115). On the sagittal images, linear and ring formed enhancements were seen in 10 (27.0%) and 17 (63.0%) NMOSD patients respectively. The enhancements in long-segment DCM patients had transvers band or pancakelike appearance in 15 (50%) patients and irregular flake appearance with longitudinally oriented long axis in 15 patients (50%). Conclusions: By analyzing the number, length, location, and form of the gadolinium enhancements, NMOSD and long-segment DCM could be well differentiated.